If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(v + 2) + -6v = 24 Reorder the terms: 2(2 + v) + -6v = 24 (2 * 2 + v * 2) + -6v = 24 (4 + 2v) + -6v = 24 Combine like terms: 2v + -6v = -4v 4 + -4v = 24 Solving 4 + -4v = 24 Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + -4v = 24 + -4 Combine like terms: 4 + -4 = 0 0 + -4v = 24 + -4 -4v = 24 + -4 Combine like terms: 24 + -4 = 20 -4v = 20 Divide each side by '-4'. v = -5 Simplifying v = -5
| 18x-7x-10x=2 | | 44(3+c)+c=c+4 | | p-p+p-p+4p=12 | | -30=4(u-8)-2u | | 5n+1p=1.06 | | sin^2x+2cosx=1 | | -3(u+5)=4u+48 | | x-0.13x=3500 | | -8u^2+28=0 | | 40x=61x | | 2x+3y+6z=360 | | 2/3(n−5/6)=21/2 | | 16x^5-44x^4+30x^3= | | 2x+63+7x+18=90 | | 3/4x=9/10 | | 5u+14=3(u+2) | | 6+9x= | | 20-14=g | | 640=5(2)*x | | .75x=1.25x | | 0=-8p-p^2-15 | | X^3-19x-20=0 | | 7(y-4)=9y-40 | | x/5x-40*x*x-8x/7= | | 3(4x+1)=9(2x-1) | | -6n(1+10n)= | | 0=11x-3x^2-10 | | -43=6b+8 | | 125m-100m+38800=40200-175m | | -6(x+3)-12=17+7 | | 1.39=ln(y) | | 6a^2-a-15= |